Analisis Faktor yang Mempengaruhi Ketimpangan Distribusi Pendapatan di Pulau Jawa Tahun 2010-2015 - Syilviarani, Anis Tunas; , Ir. Maulidyah Indira Hasmarini, MS (2017)
This research aims to analyze the effect of inflation, the HDI, GDP, unemployment rate, income distribution inequality toward UMR in Java. This type of research data for the time series. The sample in this study was 6 provinces. Income inequality was measured using the Gini index of income inequality and the results show there is highest in the provinces of Yogyakrta and the lowest income inequality exists in Central Java province. Methods of data analysis used in this study is the regression of the panel. The most appropriate model of diipilih in this research are Pooled Ordinary Least square (PLS). Based on the results of the test of the existence of a Model, simultaneously variable inflation, HDI, GDP, unemployment rate, UMR effect on inequality and income distribution in Java years 2010-2015. Determinant of the coefficients of test results show that magnitude of R-square value of 0.566813 or of 56.68%. This means that the variation of the Gini index can be explained by the independent variable that is in statistical models such as (inflation, HDI, GDP, unemployment rate, UMR). While the rest of 43.32% explained by other factors that are not included in the model.